Partially coherent UV–VIS light generation in photonic crystal fiber using femtosecond pulses - Miglė Kuliešaitė (Elsevier, 2021)
Light generated in optical fibers due to various nonlinear processes often has a broad spectrum and is commonly considered as a potentially convenient source of seed for tunable wavelength laser systems and many other applications. The nonlinear processes usually considered when discussing this spectrum broadening are coherent.In this paper we present experimental and theoretical investigation of a partially coherent nonlinear phenomenon occurring at the same time — ultraviolet–visible light (375 nm–500 nm) generation in a short photonic crystal fiber pumped by ∼110fs duration and 1028 nm wavelength pulses.